"Balloon to Platform Framing": a change of the 1880s? - Isaacs, Nigel (Architectural History Aotearoa, 2021)
Brett’s Colonists’ Guide and Cyclopaedia of Useful Knowledge: Being a Compendium of Information by Practical Colonists, edited by Thomas W. Leys, was first published in 1883. Rated, in 1993 in a National Library Exhibition, as one of the 21 "Working Titles" that had shaped New Zealand, it provided "all Information of possible use" to new arrivals. This included how to build your own cottage – providing floor plans, a material list and an estimate of labour for four cottages (increasing to five cottages complete with a set of written specifications in the 1897 edition). These designs and quantities provide a unique opportunity to explore changes in the technology of New Zealand house construction. It has been hypothesised that in the 1890s timber construction shifted from balloon to platform framing – the basic style still used for timber framed houses. The paper will report research that examined import statistics, business records and quinquennial national censuses to explore indirect measures of changes in construction technology. It is concluded that this change occurred in the previous decade, the 1880s.